2023
DOI: 10.3390/toxics11100835
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Health Risk Assessment of Sulfonamide Antibiotics in Different Freshwater Fish in Northeast China

Mengnan Shen,
Bowen Yu,
Yi Hu
et al.

Abstract: This study aimed to investigate the levels of 12 sulfonamide antibiotics in freshwater fish species obtained from three cities in northeastern China (Harbin, Changchun, and Shenyang). The analysis was conducted using HPLC–MS/MS to accurately quantify the antibiotic concentrations in the fish samples. The results showed that the average levels of sulfonamide antibiotics in fish samples from Harbin, Changchun, and Shenyang were 1.83 ng/g ww, 0.98 ng/g ww, and 1.60 ng/g ww, respectively. Sulfamethoxazole displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Additionally, a recent study conducted in Argentina on fish revealed that the estimated dietary exposure to multiantibiotic residues in commercial fish did not surpass the acceptable daily intake [ 16 ]. Unlike the present study, the acceptable daily intake of antibiotics for individuals consuming fish in Changchun and Shenyang was determined to be lower than the EDI value for Yellow Sea fish (0.065 μg/kg bw/day) [ 66 ]. The HQ values for antibiotics also varied between 2.30 × 10 −7 and 7.14 × 10 −4 .…”
Section: Resultsmentioning
confidence: 68%
“…Additionally, a recent study conducted in Argentina on fish revealed that the estimated dietary exposure to multiantibiotic residues in commercial fish did not surpass the acceptable daily intake [ 16 ]. Unlike the present study, the acceptable daily intake of antibiotics for individuals consuming fish in Changchun and Shenyang was determined to be lower than the EDI value for Yellow Sea fish (0.065 μg/kg bw/day) [ 66 ]. The HQ values for antibiotics also varied between 2.30 × 10 −7 and 7.14 × 10 −4 .…”
Section: Resultsmentioning
confidence: 68%